Diseño e implementación de un sistema de transmisión, análisis y presentación de datos para la estación meteorológica; del laboratorio de energías alternativas, del Área de Energía, Las Industrias y los Recursos Naturales no Renovables de la Universidad Nacional de Loja. - Pillco Pillajo, Remigio Alvino (2006)
This research work, was developed with the aim of implement a system for data transmission via the GSM / GPRS network, the CONECEL company. To access this network, the GPRS service is hired, SIM Card acquisition and the acquisition of equipment for transmission MODEM AND ROUTER wireless data GPRS. The system as a whole, will to transmit data (telemetry) between the City of Zapotillo and Laboratory Alternative Energy Area Energy's National University of Loja.   The telemetry system implemented, making the data processed by the computer DATALOGGER data acquisition, meteorological station and Zapotillo sends to Loja; the information stored in the memory of the logger can get on a PC via its RS-232 serial digital interface. The datalogger contains a application software, which is installed on the PC, the same as using commands this allows you to set and read data from memory and download them in a text file type. The process of reading data from the DATALOGGER mounted on the station weather; from the laboratory, it is done by the router and MODEM WIRELESS GSM / GPRS; the first to be assembled in the monitoring station Zapotillo which has the serial RS - 232 and the second with USB port It is mounted next to the PC lab.   The software for analysis and presentation of data concerning the behavior of the solar and wind energy, is designed by the manufacturer of the datalogger and our case designed by the Company, the same that was rented for effect test.